Implementation of the policy of external reference pricing for medicines: a review of international approaches - Sholoiko, N. V.; Nizhenkovska, I. V.; Babenko, M. M.; Hala, L. О.; Datsiuk, N. O. (Social Pharmacy in Health Care, 2023)
External Reference Pricing (ERP) for medicines is one of the most widely adopted pharmaceutical pricing policies applied by countries with varying income levels for many years. The policy of ERP is aimed at minimizing drug costs and improving the accessibility of effective treatments to the population. According to experts, the inefficient implementation of the ERP system may hinder the introduction of new and innovative medicines into the country’s market. Aim. To review and summarize the scientific literature data on international approaches to implementing the policy of ERP on medicines. Materials and methods. The data from the London School of Economics (LSE), materials from the European Medicine Price Database (Euripid), the World Health Organization (WHO), the USAID “Medicines, Technologies, and Pharmaceutical Services (MTaPS)” program, and international scientific publications regarding the implementation of ERP worldwide were reviewed and summarized. Results. When reviewing international approaches to ERP, a number of important implementation criteria were identified. There were transparent criteria for selecting reference countries, the use of manufacturer prices, the methodology for calculating the reference price, data sources used, consideration of GDP differences and exchange rate fluctuations, as well as regular price revision. It was found that most countries used manufacturer prices to compare the cost of medicines. The average value formula for calculating the reference price was most commonly applied, but some countries used the lowest prices in the reference countries. Not all countries took into account GDP and currency exchange rate fluctuations, which could lead to artificially inflated prices. Availability of reliable data is a key factor and, unfortunately, remains one of the main barriers to making pricing decisions. Recently, there has been a tendency to shift the focus from ERP to value-based pricing using health technology assessment (HTA). It reflects the desire to optimize drug costs while maintaining the treatment quality. The analysis of various countries worldwide based on the 14 principles of effective ERP implementation proposed by Sullivan, Kanavos, and Kalo in 2015 showed that there was a positive correlation between ERP models and per capita income since the higher the per capita income, the more countries adhered to these 14 principles. This may be explained by the fact that higher income signifies less dependence on cost-minimization practices. Conclusions. Currently, the use of ERP is the most widespread drug pricing policy in the world, despite the growing trend of value-based pricing using HTA. In the study, it has been found that each country has specific approaches to ERP, which are determined by the economic situation and reimbursement methods. Unfortunately, no country fully complies with all 14 principles of effective ERP implementation. Systematic monitoring of the results of ERP implementation and updating it based on the results obtained is a fundamental component of effective use of this drug pricing policy. Further research development is seen in the analysis of the current state of ERP implementation for medicines in Ukraine.